Direito do trabalho na era da descentralização produtiva - Calvet, Otavio Amaral (2015)
The productive decentralization, phenomenon through which occurs the outsourcing of part of the demanded productive activity through the hiring of third-party (legal or natural persons) with maintenance of some sort of control, in a greater or lesser degree, focused on the production output for partner companies, constitutes a reality. If on one hand the productive decentralization is a business development model, on the other it has demonstrated in certain cases to be a factor of casualization of human labor, as in face of the globalization phenomenon and new forms of communication, often decentralization occurs in countries still under a low level of legal protection, with reduced cost of labor and scarce or ineffective labor legislation. In this new scenario of business structuring, it remains evident the gap in which stands the legal system to produce effective protection to the working human being and allow economic development, considering recognition as a fundamental principle of the Republic not only the dignity of the human person, but also the social value of the work and the free initiative. It is noticed that this new reality of the labor market adjustment advances while the Labor Law struggles to stay untouched, creating a growing gap between labor regulation and the current needs of workers and companies, urging the recognition of new forms of accountability of the actors in the production chain who benefit from this system and, ultimately, of their own work energy, even from a distance and without a direct formal link; on the other hand, it urges the promotion of good practices that can lead to gain in productivity and economic development. It is proposed in this paper, therefore, a new approach to Labor Law, with criteria for characterization of the productive decentralization phenomenon, focusing on cases in which there may be legal accountability towards employees of subcontracted companies by the main company, delimiting the application of labor law in the era of post-positivism inserted in the legal system of a Democratic State of Law